Women-Led Enterprises in Turkey - Cebeci, Tolga; Essmat, Sammar (World Bank, Washington, DC, 2016)
The Business Environment and Enterprise Performance Surveys 2013 (BEEPS orEnterprise Surveys) conducted by the World Bank provides new opportunities to betterunderstand obstacles to female entrepreneurship in Turkey and thereby develop morefocused policies to improve it. The last BEEPS for Turkey, conducted between January 2013 and May 2014, covers 1,344 enterprises that employ at least 5 people and operate in industry or services all around Turkey. Those who are identified as “the top manager”,“the main decision maker” and “owner/one of the owners (by any share in the capital)of the enterprise” in the survey are referred to as the “leader of the enterprise” for the purpose of this study. It is well documented that participation of women in economic life in Turkey is too lowboth compared to that of men in the country and that of women in countries of similarper capita income. This gender gap in economic participation is observed not only inparticipation in the labor market, but also in entrepreneurship. Although women in most countries lag behind men in entrepreneurship, the gap is particularly large in Turkey.Achieving gender equity in economic life is one of the main areas covered by the Turkey Country Partnership Strategy of the World Bank Group. One of the projects that the Bank has been implementing together with the Ministry of Family and Social Policies tothis end is the “Increasing Women’s Access to Economic Opportunities”. This study aims to contribute to the project by identifying and analyzing gender aspects ofentrepreneurship in Turkey. In addition to the main survey that includes questions about the business environment, a separate module on gender was included in the 2013 Turkey survey. The purpose of the gender module was to get a better understanding of the profiles and performance of enterprises led by women as well as the profiles of what we define as womencompany leaders. The outline of this study is as follows: The second section compares profiles ofentrepreneurs led by men versus those led by women. So, the basic characteristics ofenterprises are compared by gender of the leader. The third section compares theprofiles of the company leaders themselves. The forth section analyzes performances ofenterprises by gender of the leader and finally the fifth section analyses the perceptionof business environment constraints by gender of the business leader.